PERAN KONTRAK PSIKOLOGIS KONSUMEN TERHADAP BRAND LOVE DAN POSITIVE WORD OF MOUTH DALAM MEMENGARUHI REPURCHASE INTENTION KONSUMEN BENGKEL MOBIL X - Ichwandi, Valencia Novita; Immanuel, Dewi Mustikasari (Ma Chung Press, 2024)
The purpose of this research is to analyze the influence of Transactional Psychological Contracts, Relational Psychological Contracts, Brand love, Positive Word of Mouth, and Repurchase Intention on Bengkel Mobil X. This research uses a quantitative approach, data collection is carried out through the distribution of online questionnaires to 230 respondents who have met the criteria. The sampling technique used is non-probability sampling. In this study, the results of data processing were tested using Smart-PLS 3.0. The results of this study show that Transactional Psychological Contact and Relational Psychological Contracts have a positive and significant influence on Brand love and Positive Word of mouth, likewise with Brand love and Positive Word of mouth towards Repurchase Intention. Keywords: Transactional Psychological Contracts, Relational Psychological Contracts, Brand love, Positive Word of mouth, Repurchase Intention.